PERLINDUNGAN HUKUM PEMEGANG HAK TANGGUNGAN TERHADAP BARANG JAMINAN YANG DISITA OLEH KANTOR PAJAK - FITRI TRISNASARI NASUTION (PREMISE LAW JURNAL, 2016)
Based on Article 21 of UUKUP, the State has the authority to dun tax early although hypothecation is attached on the confiscated object so that the position of creditor as the hypothecation holder who has preference right on debtor’s debt is weak. The research used judicial normative and statute approach. The result of the research showed that collateral with hypothecation on it confiscated by the State will not eliminate its droit de suite of the collateral according to Article 7 of UUHT which states that hypothecation will not end although it is transferred to another party (in this case it is confiscated by Tax Office). By the binding of hypothecation, the authority on the collateral is transferred to creditor to execute it when debtor is not able to pay off his debt. The right of the collateral owner will be returned when hypothecation is cancelled because the loan has been paid off. Keywords: Hypothecation Protection, Taxes Payable, Collateral